Effect of different packages in the storage of yellow araçá (Psidium cattleianum Sabine) mass candy sweetened with xylito (Revista Brasileira Multidisciplinar, 2021)
The study of the stability of new products from the processing of underutilized native fruits is essential for the development of the national industry. The objective was to evaluate the effect of different packages on the physico-chemical stability of yellow araçá mass candy sweetened with xylitol. The araçá pulp was evaluated for physical-chemical quality parameters and proceeded to candy processing. The candy was made with 60% pulp, 40% xylitol, 2% low methoxylation pectin and 0.12% calcium chloride, being packaged in four types of packaging (polypropylene, glass, PVC film and film PVC covered with aluminum). The stability of the candy was evaluated during 90 days of storage at room temperature (27.5 ºC), and quality analyzes were performed every 30 days. The water content and total solids of the candies differed significantly between the types of packaging for the times of 30, 60 and 90 days. Thus, the migration of water to the environment occurred more easily in candies packed in polypropylene, film PVC covered with aluminum and PVC film, due to the physical characteristics of the polymeric matrix of plastic packaging. For the pH, between 30 and 90 days of storage,only the film PVC covered with aluminum packaging was not stable. It is inferred that the araçá mass candy is an innovative product, and that storage at room temperature in transparent glass packaging with a metallic lid for up to 90 days is the most viable.
Keywords: Fruit Candy; Physico-chemical Stability; Native Fruit